PENGARUH PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP PERILAKU MORAL SISWA KELAS XI SMKN NGRAHO, KECAMATAN NGRAHO, KABUPATEN BOJONEGORO - Fifi Rahmawati; Raden Roro Nanik Setyawati; Siti Maizul Habibah; Walib Abdullah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of digital technology has made social media, particularly TikTok, an integral part of adolescents' lives and has the potential to influence their thinking, attitudes, and moral behavior. This study aimed to examine the relationship between TikTok social media use and the moral behavior of eleventh-grade students at SMKN Ngraho, Ngraho District, Bojonegoro Regency. This research employed a quantitative approach with a correlational design. The population consisted of 120 eleventh-grade students in the 2025/2026 academic year, with a sample of 93 students selected using simple random sampling based on the Slovin formula. Data were collected through a Likert-scale questionnaire and analyzed using validity, reliability, normality, linearity, and Pearson Product Moment correlation tests with SPSS. TikTok usage was measured through usage intensity, duration, access frequency, content type, and user activities, while moral behavior was assessed through honesty, responsibility, respect, empathy, and compliance with social norms. The results revealed a positive and significant relationship between TikTok use and students' moral behavior, with a correlation coefficient of 0.616 and a significance value of <0.001. Therefore, the alternative hypothesis was accepted. These findings highlight the importance of parental and teacher supervision as well as digital literacy in encouraging students to use social media wisely, responsibly, and in ways that support moral development.